Tailoring Oxygen Vacancy of Co3O4 Microcubes by Annealing Co3[Co(CN)6]2 Template in Air for Ultrasensitive Humidity Mapping. Issue 2 (4th February 2022) - Yu, Haixia; Guo, Chuanyu; Zhang, Xianfa; Cheng, Xiaoli; Xu, Yingming; Gao, Shan; Huo, Lihua
Abstract : Tailoring Oxygen Vacancy Fabricating oxygen vacancy on surface of metal oxides is performed as an effective strategy to improve the humidity sensitivity of materials even under low humidity level. This provides more possibilities for the application of low‐cost humidity sensors in some emerging fields in terms of intelligent skin, human‐machine interface, contactless screen, etc. More details can be found in article number 2100166 by Yingming Xu, Lihua Huo, and co‐workers.